2012
DOI: 10.12659/msm.882895
|View full text |Cite
|
Sign up to set email alerts
|

Induction of osteoporosis with its influence on osteoporotic determinants and their interrelationships in rats by DEXA

Abstract: SummaryBackgroundAs women are the population most affected by multifactorial osteoporosis, research is focused on unraveling the underlying mechanism of osteoporosis induction in rats by combining ovariectomy (OVX) either with calcium, phosphorus, vitamin C and vitamin D2/D3 deficiency, or by administration of glucocorticoid (dexamethasone).Material/MethodsDifferent skeletal sites of sham, OVX-Diet and OVX-Steroid rats were analyzed by Dual Energy X-ray Absorptiometry (DEXA) at varied time points of 0, 4 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 35 publications
2
37
0
2
Order By: Relevance
“…The osteoporotic induction applied over several months allows a tracking of the degradation of the bone which comes along with a reduction of the bone mineral content and density [18]. In a previous study these results were confirmed by a semi quantitative analysis of the Ca content [11].…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…The osteoporotic induction applied over several months allows a tracking of the degradation of the bone which comes along with a reduction of the bone mineral content and density [18]. In a previous study these results were confirmed by a semi quantitative analysis of the Ca content [11].…”
Section: Resultsmentioning
confidence: 67%
“…Beside this a remarkable and statistical significant reduction of about 50% of the HAP content for the osteoporotic animals (OVX + diet group) can be found. However, the extreme reduction revealed by ToF-SIMS measurements is plausible and a qualitative comparison with BMD evaluated by DEXA measurements shows the same tendencies although not to this extent [18]. Due to the experimental conditions, like the Ca and Vitamin D deficient diet, wide regions of the trabeculae are not mineralised anymore, which indicates rather osteomalacia than osteoporosis.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…In a previous study we have shown that enhanced osteoporotic effects ( scores below −2,5, reduced bone mineral density and bone mineral content measured by means of Dual Energy X-ray Absorptiometry, DEXA) could be seen in rats by combining ovariectomy with calcium, phosphorus, vitamin c, and vitamin D2/D3 deficiency over a period of 12 weeks [4]. However, little information is available about mesenchymal stem cells (MSCs) residing in the bone marrow of the "osteoporotic" rats.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we therefore focused on characterization of rat MSC three months after osteoporosis had been induced experimentally [4]. Investigations in vitro have been done in order to evaluate putative cellular changes of rat MSC regarding their proliferation, migration, and differentiation capacity.…”
Section: Introductionmentioning
confidence: 99%